2019
DOI: 10.1071/rd18278
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific diversity of testes mass and sperm morphology in the Philippine chrotomyine rodents: implications for differences in breeding systems across the species

Abstract: The high diversity of native Philippine murid rodents includes an old endemic group, the chrotomyines, which are the sister group of the Australasian hydromyines. Herein we detail their interspecific diversity of relative testes mass (RTM) and sperm morphology. We find that in chrotomyines, as in the Australasian hydromyines, testes mass relative to body mass differs by an order of magnitude across the species and ranges from a large RTM in Soricomys and Chrotomys species to a small RTM in Apomys. Sperm morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…There seems to be coevolution between sperm form and sperm size. Thus, an increase in sperm head complexity is accompanied by an increase in total sperm length, as originally pointed out by our group (Roldan, Gomendio, & Vitullo, ), and both are coevolving under the influence of sperm competition (Breed et al., ; McLennan et al., ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sesupporting
confidence: 68%
See 1 more Smart Citation
“…There seems to be coevolution between sperm form and sperm size. Thus, an increase in sperm head complexity is accompanied by an increase in total sperm length, as originally pointed out by our group (Roldan, Gomendio, & Vitullo, ), and both are coevolving under the influence of sperm competition (Breed et al., ; McLennan et al., ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sesupporting
confidence: 68%
“…the so‐called hook) also shows that both its length and angle are influenced by sperm competition (Immler, Moore, Breed, & Birkhead, ; Varea‐Sánchez, Tourmente, Bastir, & Roldan, ). A series of recent comprehensive analyses of Australian rodents, a group in which several appendices have evolved in the sperm head, showed that several head parameters associate with levels of sperm competition (Breed et al., ; McLennan, Lüpold, Smissen, Rowe, & Breed, ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sementioning
confidence: 99%
“…Other species in the Pogonomys and Mallomys divisions in the genera Abeomelomys, Anisomys, Xenuromys, and Mammelomys, as well as that of Lorentzimys, have a sperm head in which the ventral processes are entirely absent but the apical process is generally longer than that of most other hydromyine rodents. The presence of a single apical process is similar to that of sperm morphology of various other genera of murid rodents that occur in Southeast Asia and the Philippines (Breed & Yong, 1986;Breed & Musser, 1991;Pahl et al, 2018;Breed et al, 2019) including species that are members of the Chrotomys division in the hydromyine tribe as well as members of the Maxomys, Dacnomys, and Bunomys divisions of the Rattini (Rowe et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…These authors explained that in the absence of sperm competition, spermatozoa seem to degenerate and sperm quality decreases dramatically but it is still sufficient to fertilize. Several recent studies on other mammalian and bird species similarly related the presence of a high percentage of abnormal spermatozoa to potentially relaxed sperm competition and a monogamous mating system (Breed et al, 2018; Humann-Guilleminot et al, 2018; Peirce et al, 2018). Dorman et al (2013) indicated that there seems to be co-evolution of the gametes to aid sperm-zona interactions in the Bandicoot rat ( Bandicota indica ), where a low level of sperm competition is also apparent.…”
Section: Discussionmentioning
confidence: 99%